NaIO4/LiBr-Mediated direct conversion of benzylic alcohols and aromatic aldehydes to aromatic esters - Shaikh, Tanveer Mohammad Ali; Emmanuvel, Lourdusamy; Sudalai, Arumugam (Synthetic Communications, 2007)
Aromatic aldehydes or benzylic alcohols are directly converted to the corresponding aromatic esters in high yields on treatment with methanol or ethanol mediated by sodium metaperiodate (NaIO4)/LiBr in an acidic medium.
Keywords: aromatic ester; benazaldehyde; Benzyl alcohol; Lithium bromide; Sodium metaperiodate